Transnational Cultural Belonging of Bangladeshi Migrants in South Korea (Халықаралық қатынастар және халықаралық құқық сериясы, 2023)
Belonging to one’s homeland is common and universal for human beings. Transnational culture belonging is the practices and actions of some elements such as language, food, clothes, song, etc. that refers to a person's sense of belonging to a particular culture or place. This study aims to examine transnational cultural belonging among Bangladeshi migrants in South Korea. A quantitative study was conducted based on 310 surveys on Bangladeshi migrants in South Korea during six months from March 2016 to August 2016. The results show that Bangladeshi migrants in South Korea have strong transnational cultural belonging to their homeland. The highest degrees of transnational cultural belonging were found “talking in their native language” and “eating traditional food” in cultural originality belonging and “watching Bangladeshi television” in cultural entertainment belonging. The results support the studies of Bangladeshi migrants in western countries as strong transnational belonging at homeland. This study suggests subsequent studies to compare transnational cultural belonging of various migrant groups through sampling based on socio-demographic factors.Key words: Bangladeshi migrant, international migration, Bangladesh, South Korea, transnational cultural belonging